LIFE AND WORK OF THE LVIV ALCHEMIST ANDRZEJ TOROSOWICZ - Vitalii Shchepanskyi (Cхід, 2018)
The article covers the life and work of the Lviv bourgeois Andrzej Torosowicz who was the natural philosopher of the early modern period. Separately is given a description and a brief analysis of his treatise "Secrets of the philosophical garden truthfully gathered about the blessed philosophical stone" (1626-1631).